Performance assessment of industrial-sized solid oxide cells operated in a reversible mode: Detailed numerical and experimental study. (30th October 2020) - Subotić, Vanja; Thaller, Thomas; Königshofer, Benjamin; Menzler, Norbert H.; Bucher, Edith; Egger, Andreas; Hochenauer, Christoph
Abstract: Reversible solid oxide cells (rSOCs) present a unique possibility in comparison to other available technologies to generate electricity, heat and valuable fuels in one system, in a highly-efficient manner. The major issue hindering their commercialization are system reliability and durability. A detailed understanding of the processes and mechanisms that occur within rSOCs of industrial-size, is of critical importance for addressing this challenge. This study provides in-depth insight into behavior of large planar rSOCs based on a comprehensive experimental and numerical study. All the numerical data obtained are validated with the in-house made cells and experiments. The sensitivity analysis, which covers a wide range of operating conditions relevant for industrial-sized systems, such as varying operating temperature, H2 /H2 O-ratio, operating current etc., provides very good accordance of the cell performance measured and simulated. It reveals that lowering fuel volume and thus causing fuel starvation has more pronounced effect in an electrolysis mode, which is visible in both the low-frequency and the middle-frequency range. Moreover, both co- and counter-flow are appropriate for the reversible operation. However, more uniform current density distribution is achievable for the counter-flow, which is of crucial importance for the real system design. The most accurate performance prediction can be achieved when dividing the cell into 15 segments. Slightly lower accuracy is reached by logarithmic averaging the fuel compositions, thus reducing the calculation time required. A computationally- and time-efficient model with very precise performance prediction for industrial-sized cells is thus developed and validated. Highlights: Time-efficient spatially-resolved model for industrial-sized rSOCs. Detailed performance assessment based on numerical and experimental study. Model validation based on in-house made cells and experiments. Very good accordance between measured and simulated EIS, DRT and U/i data. Comparison of co-flow and counter-flow conditions for rSOC operation.